A combination of EFG-SBM and a temporally-piecewise adaptive algorithm to solve viscoelastic problems. (June 2016) - Guo, X.F.; Yang, H.T.
Abstract: This paper combines Element-Free Galerkin Scaled Boundary Method (EFG-SBM) with a temporally-piecewise adaptive algorithm to solve viscoelastic problems. By expanding variables at a discretized time interval, the variations of variables can be described more precisely, and a space-time domain coupled problem can be converted into a series of recurrent boundary value problems which are solved by EFG-SBM via an adaptive computing process. Numerical tests including creep and relaxation are given to verify the proposed algorithm.